‘Senses’: Assessing a Key Term inDavid Chidester’s Analysis of Religion - Johan M. Strijdom (Journal for the Study of Religion)
The purpose of this article is to illustrate and assess Chidester’suse of the ‘senses’ as an analytical term in his study of religion. Under ‘senses’ Chidester includes not only the five conventional senses of Aristotle, but also analyzes metaphorical uses of the senses in religious discourse, the visions and dreams of mystics and shamans, and eventually new media as extensions of the human senses. Chidester’s analysis of the senses in European Christian discourses on the one hand, and in colonial and postcolonial African indigenous religion and imperial religious studieson the other hand, is compared and assessed. Although he does not offer a systematic comparison of these case studies, I argue that his analysis lends itself to an explicit comparison of the senses as material aspects of religion and showhow his contextualized and historically nuanced analysis of the senses in religion and religious studies informs a critical study of religion. Since criticalassumes judgment, values need to be explicated in terms of critical theories, which in my view need further elaboration.